Depression, Substance Use, and Demographic Correlates among University Students: A Cross- Sectional Study among Students in Higher Educational Institution - Bala Ganesh Pichamuthu; Kalpana Kosalram; Sathya Thennavan; Sharmila Govardhanan (Addicta: The Turkish Journal on Addictions)
Students studying in higher education institutions are in an important life stage. It is usually the time when many students face pressures, which may lead to substance use disorders and mental health issues. The study aimed to determine the relationship between alcohol consumption, smoking, tobacco use, and depres- sion among university students. A cross-sectional survey was conducted among 4059 university students from multiple higher educational institutions, from June 2022 to January 2023. Data were collected through self-administered questionnaires, including the Patient Health Questionnaire-9 for assessing depression. Associations of substance use (alcohol, smoking, and tobacco) with depression were evaluated using logistic regression analysis, adjusting for demographic variables. The prevalence of depression in the study popula- tion was significantly associated with smoking and tobacco use. The odds for depression in smokers were 1.604, with a 95% CI of 1.163–2.213, and p = .004; and odds ratio of 1.106 with a 95% confidence interval of 0.721–1.696 for tobacco users, with p = .643. Alcohol consumption, at first, was associated with increased odds of depression among non-drinkers, with an odds ratio of 1.446 and a 95% confidence interval of 1.095– 1.910 (p = .008); however, the association was adjusted for other variables with an odds ratio of 0.772 and p = .080. Besides, male students and those who received lower monthly pocket money were more likely to have depressive symptoms. Logistic regression analysis of the three variables of depression shows that gender, smoking, and financial status are predictors of depression. Pocket money is a strong predictor of it (p < .001). In this paper, we establish the relationship between substance use and depression in university students. In general, an increased level of depression was always associated with smoking and tobacco use, and the relation between alcohol consumption and depression showed interaction with other psychosocial variables. These results point to the need for targeted mental health interventions within the university set- ting, dealing with both substance use and depression.